ALLOCATIVE EFFICIENCY AND QM FACTORS COVARIATE IN SERBIAN INDUSTRY - Spasojević-Brkić, Vesna K; Dondur, Nikola; Pokrajac, Slobodan; Josipović, Sonja (Journal of Applied Engineering Science, 2012)
Trends of allocative efficiency and covariate of firm size and efficiency of quality management(QM) factors in the Serbian industry were tested on the unbalanced panel sample of 48 industrial firms from 12 industrial sectors in the period 2004-2009. The obtained results show that 10 of 12 sectors have a positive covariate of participation in the output market and multi-factor productivity. Covariates of firm size and efficiency of all QM factors record the same direction in the chemicals sector (positive) and motor vehicles (negative), which means that in those two sectors larger companies had above-average and/or below-average efficient TQM. The same (positive) trend of allocative efficiency and covariates of all QM factors was recorded in manufacture of chemical industry.
Keywords: QM; Industry; Covariation; Allocative efficiency; allocation